Effectiveness of warm compress and cold compress to reduce laceration perineum pain on primiparous at Candimulyo Magelang 2015 - Purwaningsih, Agustina Ayu; Rahayu, Heni Setyowati Esti; Wijayanti, Kartika (International Journal of Research in Medical Sciences, 2017)
Background: The problem that most felt the presence of perineal laceration was pain. In the postpartum mothers experience pain because of perineal lacerations cause unpleasant effects such as pain and fear to move, so it can cause many problems. The solve of this problem can be administered with pharmacologic therapy and nonpharmacologic therapy. Non-pharmacologic therapy can be given to reduce pain include stimulation of the skin, giving warm and cold compresses. Warm compress is the act of giving a sense of warmth to the client specific parts of the body and a cold compress is provide a sense of cold on the client by using ice water on the body that feels pain. Objective of the study was to determine the effectiveness of warm compress and cold compress against the perineal laceration primiparous. Methods: This study using Quasi Experiments with two group pretest and posttest with Mann Whitney test. Total sample is 36 people, 18 people warm compresses and 18 people cold compresses, by using accidental sampling technique. Techniques warm compresses and cold compresses performed three times during one day. Results: This study shows that there is a difference between therapeutic warm compresses and cold compresses. Conclusions: Cold compress more effective in reducing laceration perineum pain on primiparous.